Reducing nitrate content in lettuce using polyolefin-coated fertilizers - Ombódi, A.; Saigusa, M. (International Journal of Horticultural Science, 2000)
Pot experiments were conducted in order to investigate the effects of the controlled-release characteristic, nitrogen form and application method of polyolefin-coated fertilizers on the nitrate content and yield of lettuce (Lactuca sativa L.). Comparing broadcast application of polyolefin-coated urea (POCU) and urea at four fertilization levels, it was found that application of POCU decreased the nitrate content and increased the yield, due solely to its controlled-release characteristic. Comparing band applications of POCU or polyolefin-coated diammonium-phosphate (POC-DAP) to broadcast application of ammonium nitrate, it was found that a band application of both urea and ammonium containing polyolefin-coated fertilizers can decrease nitrate content in lettuce, without causing any significant yield decrease. This was a combined effect of the controlled-release characteristic and realized ammonium nutrition. Comparing effects of broadcast, band and spot applications of POC-DAP, it was found that nitrate content, was the lowest in the spot application treatment. However, considering both nitrate content and yield, band application was found to be the most effective application method.